Previous in Relation and Functions Next in Relation and Functions | ||
Question Number 131573 by mathlove last updated on 06/Feb/21 | ||
$$\:{if}\:\:\:\:{f}\left({x}+\frac{\mathrm{1}}{{x}}\right)={x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} }\:\:\:\:\:{then}\:\:{faind}\:\: \\ $$$${f}\left(\frac{\mathrm{1}}{{x}}\right)=? \\ $$ | ||
Answered by rs4089 last updated on 06/Feb/21 | ||
$${f}\left({x}+\frac{\mathrm{1}}{{x}}\right)={x}^{\mathrm{3}} +\frac{\mathrm{1}}{{x}^{\mathrm{3}} } \\ $$$${f}\left({x}+\frac{\mathrm{1}}{{x}}\right)=\left({x}+\frac{\mathrm{1}}{{x}}\right)\left({x}^{\mathrm{2}} +\frac{\mathrm{1}}{{x}^{\mathrm{2}} }−\mathrm{1}\right) \\ $$$${f}\left({x}+\frac{\mathrm{1}}{{x}}\right)=\left({x}+\frac{\mathrm{1}}{{x}}\right)\left\{\left({x}+\frac{\mathrm{1}}{{x}}\right)^{\mathrm{2}} −\mathrm{2}−\mathrm{1}\right\} \\ $$$${f}\left({x}+\frac{\mathrm{1}}{{x}}\right)=\left({x}+\frac{\mathrm{1}}{{x}}\right)\left\{\left({x}+\frac{\mathrm{1}}{{x}}\right)^{\mathrm{2}} −\mathrm{3}\right\} \\ $$$${now}\:{put}\:{x}+\frac{\mathrm{1}}{{x}}\:=\:{t}\: \\ $$$${f}\left({t}\right)={t}\left({t}^{\mathrm{2}} −\mathrm{3}\right) \\ $$$${or}\:{f}\left({x}\right)={x}\left({x}^{\mathrm{2}} −\mathrm{3}\right) \\ $$$${so}\:\:{f}\left(\frac{\mathrm{1}}{{x}}\right)\:=\frac{\mathrm{1}}{{x}}\left(\frac{\mathrm{1}}{{x}^{\mathrm{2}} }−\mathrm{3}\right)=\frac{\mathrm{1}−\mathrm{3}{x}^{\mathrm{2}} }{{x}^{\mathrm{3}} } \\ $$$$ \\ $$ | ||
Commented by mathlove last updated on 06/Feb/21 | ||
$${tanks} \\ $$ | ||
Answered by mathmax by abdo last updated on 06/Feb/21 | ||
$$\mathrm{we}\:\mathrm{have}\:\mathrm{a}^{\mathrm{3}} \:+\mathrm{b}^{\mathrm{3}} \:=\left(\mathrm{a}+\mathrm{b}\right)^{\mathrm{3}} −\mathrm{3ab}\left(\mathrm{a}+\mathrm{b}\right)\:\Rightarrow \\ $$$$\mathrm{f}\left(\mathrm{x}+\frac{\mathrm{1}}{\mathrm{x}}\right)=\left(\mathrm{x}+\frac{\mathrm{1}}{\mathrm{x}}\right)^{\mathrm{3}} −\mathrm{3}\left(\mathrm{x}+\frac{\mathrm{1}}{\mathrm{x}}\right)\:\mathrm{let}\:\mathrm{x}+\frac{\mathrm{1}}{\mathrm{x}}=\mathrm{t}\:\Rightarrow\mathrm{f}\left(\mathrm{t}\right)=\mathrm{t}^{\mathrm{3}} −\mathrm{3t}\:\Rightarrow \\ $$$$\mathrm{f}\left(\frac{\mathrm{1}}{\mathrm{x}}\right)=\frac{\mathrm{1}}{\mathrm{x}^{\mathrm{3}} }−\frac{\mathrm{3}}{\mathrm{x}}\:=\frac{\mathrm{x}^{\mathrm{2}} −\mathrm{3}}{\mathrm{x}^{\mathrm{3}} } \\ $$ | ||